AB1013 Serious effects of alcohol on bone density and fracture incidence. (23rd January 2014) - Kelly, C.; Bartholomew, P.; Grapes, A.; Reddy, A.
Abstract : Background: Alcoholic liver disease (ALD) has reached almost epidemic proportions over the last decade, and has become one of the most frequent causes for seeking medical admission. It often affects relatively young people and carries significant mortality and morbidity. Whilst the effects of alcohol on the liver are well recognised, patients and clinicians are less aware of its effects on bone. There are data to suggest that alcohol does play a major role in inducing osteoporostic fractures (1) and that these carry a significant cost for health services (2). Objectives: We undertook a prospective study to assess the incidence of fractures and to measure bone density in patients with ALD. Methods: We recruited all patients admitted to the Hospital over a three month period with a diagnosis of ALD. Patients were then divided into three groups, depending on the results of their investigations: high alcohol intake, alcoholic hepatitis or established cirrhosis. The presence of any low trauma fractures within the previous two years was recorded, and bone mineral density measurements were performed at hip and spine using a Hologic Discovery C scanner. We recorded absolute BMD and T/Z scores for each site, and compared results witrh those obtained from age and gender matched controls with no evidence of ALD. Results: We identified 48 admissions with ALD over a 3 month period who were willing to be assessed. 34 were male and group median age was 47 years. Twenty patients had suffered a low trauma fracture within the previous 24 months (42%). These were widely distributed. Bone mineral density data showed no significant differences in values at either spine or hip between the three groups so data was amalgamated. Group mean Z scores at spine and hip were both significantly reduced at -0.91 (SD 1.52) [p<0.01] and -0.55 (SD 0.97) [p<0.01] respectively, when compared to controls. Men and women were equally affected and only 30% of ALD patients had normal bone density. Conclusions: Alcohol excess is strongly related to a reduction in bone mineral density, independent of whether individuals have developed reversible or irreversible liver disease. This affects both axial and cortical bone and is strongly linked to an increased risk of low trauma fracture at sites including the spine and hip. Clinicians and patients need to be aware of this association which carries significant prognostic and therapeutic implications. References: Kanis JA, Johansson H, Johnell O et al Alcohol intake as a risk factor for fracture. Osteoporosis Int 2005; 16:737–742 Lawrence T, White C, Wenn R et al. Total costs of hospital treatment for hip fractures. Injury 2005; 36: 88-91 Disclosure of Interest: None Declared